HIBAH DENGAN SYARAT BALASAN MENURUT PANDANGAN FUQAHA DAN KEDUDUKANNYA DALAM UNDANG-UNDANG SIVIL JORDAN: Conditional Hibah in Favour According to The Opinions of Islamic Jurists and Its Position in The Civil Law of Jordan - Mohamed Said, Noor Lizza; Awang, Mohd. Ridzuan; Mohd Nor, Amir Husin (Jurnal Syariah, 2019)
Conditional hibah (bequest) in favour has become a popular product in Malaysia with a market that is growing in tandem with the rapid development of the nation’s Muslim estate planning industry. Such products with the underlying conditional hibah principle need to be viewed in terms of the law, type of contract and impact on the contracting parties. However, written laws of conditional hibah in favour are still lacking in Malaysia in contrast with those provided under the Civil Law of Jordan. Therefore, this article aims to examine the views of the Islamic jurists on the conditional hibah in favour and the relevant provisions in the Civil Law of Jordan. Specific written laws for hibah are essential for regulating hibah transactions in the emerging markets so that they are consistent with the sharia principles and meet the demand of the Islamic community in this country.